PENGEMBANGAN MEDIA SUN EDUCATION PADA PEMBELAJARAN AKUNTANSI DASAR PESERTA DIDIK KELAS X PROGRAM KEAHLIAN AKUNTANSI SMK NEGERI 7 PONTIANAK - Salsa, Dini; Purwaningsih, Endang; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was do it because the learning system is still conventional with the lecture method and giving assignments or group work to students using textbooks and LKS and rarely using learning media so that students are less enthusiastic about learning. This study aims to produce Sun Education learning media so that students can more easily follow the lessons. The procedure for this study used the PPE (Planning, Production, and Evaluation) method by Richey and Klein. This data collection technique is in the form of qualitative data derived from revisions by media experts, interview data, and research questionnaires. With the results of assessments from learning practitioners and students using CVR CVI which are declared valid or suitable for use.